COVID-19 and International Political Theory - Brown, Ruairidh. author. aut Link
XII, 145 p. 1 illus.
Keywords: The COVID-19 pandemic is an international event whose impact has been acutely felt by almost everyone across the globe. Indeed, currently reading this, it is highly unlikely that your own life has not been significantly impacted by COVID-19. This book offers one of the first analysis of the COVID-19 pandemic and its potential impact from the perspective of International Political Theory. It promises normative interpretation and analysis of the COVID-19 pandemic and to map potential political orders that may emerge in the post-pandemic world. It seeks to give initial insight into how the shockwaves from this event will impact upon our political and international norms. The book focuses on the normative questions of: can emergency powers be used to preserve society from the virus without necessitating a transition to more authoritarian political norms? Will COVID-19 prove a catalyst for Chinese Socialism to challenge, and potentially usurp, liberalism as the dominant international political norm? What changes to liberalism ought to be made as a result of the pandemic? What direction should liberalism take in the post-pandemic world? Ruairidh J Brown is Head of International Relations and Political Science at Forward College, Portugal. He is currently based at Forward’s Lisbon Campus, where he teaches International Political Thought and International Relations.